Bulbous Tip Correction Focusing on Skin Soft Tissue Envelope in Asian Rhinoplasty - Da Arm Kim; Jae Yong Jeong; Sang Ha Oh (Archives of Aesthetic Plastic Surgery, 2014)
Background Correction of a bulbous tip is a difficult procedure in Asians, because their lower lateral cartilage is relatively small and structurally weak to support the thick skin soft tissue envelope (SSTE). Therefore, lower lateral cartilage manipulation alone yields inadequate bulbous tip correction. In this study, authors aim to provide a new bulbous tip definition reflecting nasal tip SSTE and categorization with a suitable surgical procedure. Methods One hundred sixty-three patients with tip rhinoplasty between January 2009 and December 2012 were studied who had a tip lobular width greater than 60% of the alar base width. Depending on cartilage size and characteristics of the nasal tip superficial musculoaponeurotic system (SMAS) with SSTE thickness, the following classifications were made: Group I: thin SSTE with a large lower lateral cartilage, Group II: thick SSTE with a small lower lateral cartilage, Group IIa: thick SSTE with loose SMAS, and Group IIb: thick SSTE with dense SMAS. We evaluated the degree of surgical improvement by comparing pre- and postoperative photographs. Results After comparing pre- and postoperative photos, we observed improvements in tip bulbosity by 11.7% in Group I (n=41), 11.9% in Group IIa (n=64), and 7.1% in Group IIb (n=58). Conclusions In Asians, nasal tip bulbosity is often due to excess SSTE. Therefore, a bulbous tip should be defined and evaluated based on its underlying SSTE. Adequate soft tissue resection in addition to lower lateral cartilage support and manipulation are warranted to achieve a refined tip.